Helping Hams' campaign kicks off for families in need - Uribes, Tom::::::::: (2013)
Fresno State President Joseph I. Castro and student body president Moses Menchaca kicked off a new campaign, Helping Hams, today at the Rue and Gwen Gibson Farm Market for families in need this holiday season.